Pengaruh Likuiditas, Debt Default, Audit Tenure, dan Ukuran KAP Terhadap Opini Audit Going Concern - Ghani, Muhammad Naufal; Utaminingtyas , Tri Hesti; Khairunnisa, Hera (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
This study aims to determine the effect of liquidity, debt default, audit tenure, and KAP size on going concern audit opinion. The independent variables analyzed are liquidity, debt default, audit tenure, and KAP size, while the dependent variable is going concern audit opinion. The research data was obtained from www.idx.co.id with a focus on the basic materials sector from 2020 to 2022. Using purposive sampling, 234 datasets were obtained from 78 companies that met the specified criteria. This study uses logistic regression analysis techniques. The results of the study indicate that liquidity, audit tenure, and KAP size have an effect on the issuance of going concern audit opinion, while debt default has no effect on the opinion.